Alcohol Consumption in China Before and During COVID-19: Preliminary Results From an Online Retrospective Survey - Wang, Yunfei; Lu, Heli; Hu, Maorong; Wu, Shiyou; Chen, Jianhua; Wang, Ling; Luo, Tao; Wu, Zhenzhen; Liu, Yueheng; Tang, Jinsong; Chen, Wei; Deng, Qijian; et al. (Frontiers in Psychiatry, 2020)
Background: Alcohol is an important aspect of the Chinese culture, and alcohol use has been traditionally accepted in China. People with stress, anxiety and depression may use more alcohol. More people reported symptoms of anxiety and depression during the outbreak of COVID-19. Thus, people may drink more alcohol during the outbreak of COVID-19 than before COVID-19. Methods: An online retrospective survey was conducted on a total sample of 2229 participants. Drinking behaviors before and during COVID-19, current risk drinking and hazardous drinking, and the association between high risk drinking and mental health problems (depression, anxiety and stress) were assessed via self-reported measures of Alcohol Use Disorders Identification Test (AUDIT) and The 21-item Depression Anxiety Stress Scales (DASS–21). Results: This study found that, compared with before COVID-19, alcohol consumption was slightly decreased during COVID-19 (from 3.5 drinkers to 3.4 drinkers, p=0.035) in overall sample. Most (78.7%) alcohol drinker were males. Before and during COVID-19, males consumed more drinkers per week (4.2 and 4.0 drinkers VS 1.3 and 1.2 drinker), had higher percentage of heavy drinker (8.1% and 7.7% VS 4.4% and 2.7%), and more drinking days per week (2.1 and 2.1 days VS 1.0 and 0.9 days). Males also had more risk drinking (43.2% VS 9.3%) and hazardous drinking (70.2% VS 46.6%) than female counterparts. This study also found that high risk drinking predicted anxiety in females.